Postpartum Pyelonephritis and Risk of Severe Maternal Morbidity - Addae-Konadu, Kateena L.; Wein, Lauren E.; Federspiel, Jerome J.; Hughes, Brenna L.; Dotters-Katz, Sarah (American Journal of Perinatology, 2021)
Objective Pyelonephritis is the most common nonobstetric cause for hospitalization during pregnancy. The maternal and obstetric complications associated with antepartum pyelonephritis are well described. However, it is not clear whether these risks extend into the postpartum period. The primary objective of this study was to describe the morbidity associated with postpartum pyelonephritis, by comparing the morbidity associated with pyelonephritis in the postpartum period to morbidity seen during pregnancy or delivery.Study Design A retrospective cohort study was performed using the Nationwide Readmissions Database (NRD), an all-payor sample of discharges from approximately 60% of U.S. hospitalizations. Discharges between October 2015 and December 2018 were included. Maternity-associated hospitalizations, diagnosis of pyelonephritis, comorbid conditions, and incidence of severe maternal morbidity were identified using International Classification of Disease-10th Revision (ICD-10) diagnosis and procedure codes. Bivariate statistics, weighted to account for the complex survey methods in the NRD, were used to evaluate the association between antepartum, delivery, and postpartum hospital stays associated with pyelonephritis and maternal morbidity. Weighted regression models were used to evaluate the association between admission timing and maternal outcomes.Results A total of 32,850 pyelonephritis admissions were identified, corresponding to a national estimate of 61,837 admissions. Of these, 1,465 (2.4%) were postpartum, 55,056 (89.0%) were antepartum, and 5,317 (8.6%) involved a delivery stay. Rates of severe maternal morbidity were higher in the postpartum group than the antepartum or delivery hospitalization groups (59.5 vs. 12.9 and 15.8%, respectively, p < 0.001); when compared with antepartum hospitalizations, the adjusted relative risk for composite severe maternal morbidity for postpartum hospitalizations was 4.68 (95% confidence interval [CI]: 4.33, 5.05). Most of this difference was driven by rates of sepsis (53.2 vs. 11.0 vs. 10.9%).Conclusion Though relatively uncommon, postpartum hospitalizations for pyelonephritis are associated with higher rates of severe maternal morbidity, driven by differential rates of sepsis, than are antepartum or delivery-associated hospitalizations.
Keywords: maternal morbidity; postpartum; pyelonephritis; sepsis